Single nucleotide polymorphisms in the development of osteomyelitis and prosthetic joint infection: a narrative review - Zhou, Jia-Qi; Liu, Zi-Xian; Zhong, Hong-Fa; Liu, Guan-Qiao; Ding, Ming-Cong; Zhang, Yu; Yu, Bin; Jiang, Nan (Frontiers in Immunology, 2024)
Currently, despite advancements in diagnostic and therapeutic modalities, osteomyelitis and prosthetic joint infection (PJI) continue to pose significant challenges for orthopaedic surgeons. These challenges are primarily attributed to the high degree of heterogeneity exhibited by these disorders, which are influenced by a combination of environmental and host factors. Recent research efforts have delved into the pathogenesis of osteomyelitis and PJI by investigating single nucleotide polymorphisms (SNPs). This review comprehensively summarizes the current evidence regarding the associations between SNPs and the predisposition to osteomyelitis and PJI across diverse populations. The findings suggest potential linkages between SNPs in genes such as IL-1, IL-6, IFN-γ, TNF-α, VDR, tPA, CTSG, COX-2, MMP1, SLC11A1, Bax, NOS2, and NLRP3 with the development of osteomyelitis. Furthermore, SNPs in genes like IL-1, IL-6, TNF-α, MBL, OPG, RANK, and GCSFR are implicated in susceptibility to PJI. However, it is noted that most of these studies are single-center reports, lacking in-depth mechanistic research. To gain a more profound understanding of the roles played by various SNPs in the development of osteomyelitis and PJI, future multi-center studies and fundamental investigations are deemed necessary.